Performance of pineapple cultivars inoculated with Fusarium guttiforme isolates on different substrates - Silva, Dayane Castro; Rodrigues, Nayara Nunes; Bertan, Fellipe Lima; Alves, João Vitor da Silva; Barbosa, Andrielle dos Anjos; Krause, Willian; Araújo, Dejânia Vieira de (Acta Scientiarum. Agronomy, 2025)
Fusariosis in pineapples causes significant losses to producers. Knowing practices that reduce disease severity is important, as cultivation in Brazil mainly relies on the susceptible cultivar ‘Pérola’. Therefore, this study aimed to analyse the vegetative development and severity of fusariosis in different pineapple cultivars inoculated with Fusarium guttiforme isolates in various substrates. Isolates were collected and inoculated into ‘Pérola’ and ‘BRS Imperial’ cultivars planted in different substrates. Vegetative characteristics and disease severity were assessed. Evaluations were carried out fortnightly over 120 days. A randomised block design was used in a triple factorial arrangement 5 x 2 x 3 (five isolates x two cultivars x three substrates). Data were analysed using Sisvar software. The cultivars showed distinct vegetative development, with ‘Pérola’ being susceptible to all isolates, displaying reduced plant height, leaf D length and width, and number of active leaves. The pineapple leaf D is used to measure plant growth and nutritional status. Isolates 3 and 7 led to the death of several ‘Pérola’ plants. The substrate that favoured the highest disease severity was composed of sand and soil in a 3:1 ratio. The ‘‘BRS Imperial’’ cultivar showed resistance to all isolates and substrates. Finally, pineapple cultivation will develop better in substrates with favourable physico-chemical compositions and proper fertilisation. The ‘BRS Imperial’ cultivar is viable for producers as it is resistant to fusariosis and can withstand abiotic stress conditions.